D-Convergence of One-Leg Methods for Stiff Delay Differential Equations (Journal of Computational Mathematics, 2021)
This paper is concerned with the numerical solution of delay differential equations(DDEs). We focus on the error analysis of one-leg methods applied nonlinear stiff DDEs. It is proved that an A-stable one-leg method with a simple linear interpolation is D-convergent of order $p$, if it is consistent of order $p$ in the classical sense.